Factors affecting consumers choice of mobile phone service providers in Kota Kinabalu / Melvin Alvarozn Michael - Michael, Melvin Alvarozn (2012)
The purpose of the study was to investigate factors affecting consumer choice of mobile service provider in Kota Kinabalu, Sabah. There are several factors that have been analysed that affect consumer to choose and subscribe a service provider in the market. For the study, Questionnaire and Exploratory Factor Analysis (EFA) method have been used to test which types of factors are the most significant factors for consumer to consider before make decision to choose which mobile services provider for their mobile services. It found that, price or rate chargers and network coverage are the most significance factors for consumer in determined to choose a mobile service provider in the market telecommunications industry. Price and network coverage of mobile phone services are the most sensitive factors which consumer consent more while making their decision.